Seismic Reliability Evaluation Strategy for Substation Systems Based on the Quasi-Monte Carlo Simulation Method and Triangle Algorithm - Xiaohang Liu; Shansuo Zheng; Qing Qin; Piji Hou (Applied Sciences)
Power systems are the backbone of modern society. As critical facilities for the transmission and conversion of electric power, substations are vital to the stable operation of power systems. Quantifying the residual seismic capacity of the substation system is an urgent issue to be addressed. Therefore, this study proposes a reliability assessment process based on network matrix algorithms and efficient simulation methods to evaluate substation systems. A typical 220 kV substation in China with 6 incoming lines and 10 outgoing lines was studied with this assessment process. The results of the case study showed that the redundancy of transformer units, due to their excessive fragility, does not effectively guarantee the complete function of the system after an earthquake. In this work, 220 kV circuit breakers, voltage transformers, and 110 kV disconnect switches were evaluated as the most vulnerable functional equipment in the substation system; improving their seismic performance can significantly improve the seismic reliability of the entire system. Furthermore, the evaluation process demonstrated that substations are more susceptible to earthquakes than individual pieces of equipment, indicating that the redundancy of existing substations is insufficient.